2023
DOI: 10.3390/su15010796
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Foam with Thermal Insulating Property Produced with the Addition of Waste Glass Powder and Rice Husk Ash

Abstract: Closed pore glass foams with dimensions of 60mm × 20 mm × 20 mm were produced using agro-industrial residues. Samples containing sodo-calcic glass powder (78%wt) and rice husk ash (16%wt) were characterized, and their technological properties were investigated. The samples were synthesized in a conventional muffle furnace at 750–800–850 °C. The results presented for apparent density (0.24–0.29 g/cm3), compressive strength (1.5–2.3 MPa) and thermal conductivity (0.021–0.025 W/mK) meet the standards for commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…In this scenario, the Circular Economy emerges as a viable model. It emphasizes the recovery and utilization of food waste [5], promotes the use of renewable resources, and supports the recycling of waste into new materials, thereby keeping them in the economic loop far longer than traditionally expected [6][7][8]. This approach not only extends the life cycle of materials but also significantly reduces pollution from production processes and improper disposal, effectively decoupling economic growth from environmental degradation [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scenario, the Circular Economy emerges as a viable model. It emphasizes the recovery and utilization of food waste [5], promotes the use of renewable resources, and supports the recycling of waste into new materials, thereby keeping them in the economic loop far longer than traditionally expected [6][7][8]. This approach not only extends the life cycle of materials but also significantly reduces pollution from production processes and improper disposal, effectively decoupling economic growth from environmental degradation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The global trend towards building taller structures has escalated concrete production, making it the most utilized material worldwide [11][12][13][14], with annual production nearing 10 billion cubic meters [15]. Research has indicated that construction processes can integrate various waste materials into concrete, such as vitreous foams [7,8], bamboo fibers [16], PET bottles [17], and glass bottles [18], to mitigate environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are organic and inorganic thermal insulation panels on the market; however, the organic ones have the disadvantage of being flammable, the fibrous inorganic ones are harmful to health, and the particulate inorganic ones densify when sintered at high temperatures, so new processing methods that incorporate controlled porosity are required [25]. However, nowadays there are ceramic foams that do not densify at high temperatures and have lower conductivities [26].…”
Section: Introductionmentioning
confidence: 99%
“…The literature presents several studies that show the potential of agroenergy residues and the importance of recycling, especially for the promotion of the regional circular economy [ 30 ]. This study evaluated the results of a biodegradable composite using natural and renewable resources, easily accessible and abundant, such as agroenergy residues that were successfully added to the matrix of biodegradable biopolymers.…”
Section: Introductionmentioning
confidence: 99%